Air infiltration in domestic refrigerators: the influence of the magnetic seals conservation - Clito Afonso (2010)
One component of the heat exchange rate in domestic refrigerators/freezers and of the other all types of refrigeration stores is the air infiltration due to the air exchange rate between inside and outside of the store trough the magnetic seals of the doors. Due to their use (opening and closing the doors) they become leaky with the time. So, it is necessary to know to measure them in a proper way in order to be able to quantify which percentage of the energy consumption of the compressor is used to overcome the air infiltration rate. In this work the tracer gas technique was used for the measurement of the air infiltration rate in a household double door commercial refrigerator. Through several tests carried out it was possible to analyse the influence of the magnetic seal conservation condition on the air exchange rates of the refrigerator. It was concluded that the air infiltration rates were strongly dependent on the door seals conservation conditions.